Primary laryngeal tuberculosis-changing trends and masquerading presentations: a retrospective study - Ponni, Satish; Venkatesan R., Sithananda Kumar; Saxena, Sunil Kumar; Suryanarayanan, Gopalakrishnan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Primary laryngeal tuberculosis is one of the common forms of head and neck tuberculosis. There is a changing trend in the manifestations of this disease and this retrospective study highlights the varying masquerading manifestations and the diagnostic and management dilemmas in managing such patients. Methods: This is a retrospective study of patients with laryngeal tuberculosis at a tertiary care hospital. Patients with primary laryngeal tuberculosis without pulmonary involvement where analyzed for the clinical manifestations, the diagnostic difficulties that where encountered and the management of these patients were analyzed. Results: Forty eight cases with laryngeal tuberculosis where identified. 12 patients with concomitant Pulmonary involvement where excluded from the study. Of the 36 patients with primary laryngeal tuberculosis 22 cases presented with atypical features like manifestation as acute epiglottitis (8 cases), mimicking laryngeal malignancy (10 cases) and polypoid lesions of the vocal cord (4 cases). Conclusions: Despite the rarity of primary laryngeal tuberculosis, a high index of suspicion is always necessary in any laryngeal lesions eluding diagnosis considering the varied manifestations of present day laryngeal tuberculosis.